Biological activity and chemical profile reported for Bauhinia forficata species (Research, Society and Development, 2022)
Objective: To describe the pharmacological properties of the species Bauhinia forficata Link in relation to its chemical constitution. Methodology: This is an integrative literature review study, which analyzes a problem by analyzing the results found in articles. The following databases were used: LILACS, IBECS, NIH-PUBMED and SCIELO, using the following descriptors (with respective translations into English) - “Bauhinia forficata” and “Plantas medicinais”. Full articles were included, available in Portuguese, English or Spanish and published between January 2016 to December 2021. Results: Nine articles made up the final sample of this study, with the highest frequency of publication in 2020 (n: 03). It was found that Bahuinia forficata Link was involved in studies that proved its antibacterial, hypoglycemic, antioxidant, anti-inflammatory, antifungal, and healing action. The hypoglycemic purpose is from more recent reviews where they showed the potential of flavonoid derivatives as innovative targets in the current management of type 2 diabetes mellitus. Conclusion: The development of this work enabled an investigation about the various benefits that the use of Bahuinia forficata Link presents to health, where knowledge about the chemical profile of this species can be extremely beneficial.